Growth, mortality and stock status of mullets (Mugilidae) in Chilika Lake, India. Issue 1 (6th April 2018) - Panda, Debabrata; Mohanty, Surya K.; Pattnaik, Ajit K.; Das, Subrata; Karna, Subodha K.
Abstract: The growth, mortality and stock status of grey mullets Chelon parsia (Ham. 1822), Chelon planiceps (Val. 1836) and Mugil cephalus (Linn. 1758) were investigated during December 2010 to November 2011 from Chilika Lake, Asia, largest brackish water lake. The length‐based analysis, using length frequency data collected from fish landing centres, formed the basic study methodology. Growth function and population parameters were studied using FAO‐ICLARM Stock Assessment Tools‐II (FiSAT‐II). The von Bertalanffy growth function (VBGF) was established as L t  = 321 mm*(1 − exp (‐0.98 year −1  × (t + 0.085 year)) for C. parsia, L t  = 315 mm × (1 − exp (−0.80 year −1  × ( t  + 0.105 year)) for C. planiceps and L t  = 700 mm*(1 − exp (−0.70 year −1 *( t  + 0.097 year)) for M. cephalus . Lower K and higher L ∞ values for M. cephalus indicated slow growth and high longevity of the species, compared to other grey mullets. Length–weight relationships were derived, indicating isometric growth for grey mullets. Recruitment of mullets was observed throughout the year, with a peak during April–July. About 50% of the mullets were caught by fishing gear before reaching their first year of age. The level of exploitation ( E  ≥ 0.60) was more than the optimum level ( E  = 0.4 for pelagic stock), indicating overexploitation of grey mullets in Chilika Lake. Moreover, the average annual yields of three mullets were observed to be higher than the estimated maximum sustainable yields (MSY), also indicating overharvesting of mullets. Thus, the mullets could be considered one of the highly overexploited resources in Chilika Lake. The findings of this study will facilitate the development of appropriate management strategies for the mullet fishery in Chilika Lake.